LEGAL BASIS OF YOUTH SPIRITUALITY IN GLOBALIZATION AND ANALYSIS OF INTERNATIONAL EXPERIENCE (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the issues of enhancing youth spirituality and forming their legal worldview in the context of globalization. The author explores the concept of "legal spirituality" as an individual's awareness of their rights and obligations, as well as education in the spirit of respect for the law. The article classifies internal and external threats affecting the minds of young people, including legal nihilism, destructive ideas in cyberspace, and religious extremism. Furthermore, it examines the role of the Development Strategy of New Uzbekistan and constitutional reforms in the legal protection of youth, while also reviewing the experiences of developed nations (South Korea, France, Singapore).